A Recursive Tuning Approach for the Model-Free PID Controller Design. Issue 4 (2018) - Wang, Jiadong; Zhang, Yanhui; Jin, Xiaoming; Su, Hongye
Abstract: This paper presents a new model-free tuning approach for the PID controller tuning with the employment of the refined recursive instrumental variable (RIV) method. The proposed approach can be applied to solve the control loop tuning problem without identification of the plant or process model and it can be implemented in the online manner. Also, the colored measurement noise has been taken into account. For PI and PID control, the implementation details and the step by step procedures are provided respectively. Two simulation examples are provided to validate the effectiveness of the proposed approach.